2010
DOI: 10.2528/pierc10061802
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Wideband Small Square Monopole Antenna With Variable Frequency Band-Notch Function

Abstract: In this paper, a novel printed monopole antenna for ultra wideband applications with variable frequency band-notch characteristic is presented. The proposed antenna consists of a stepped square radiating patch with modified W-shaped slot and a ground plane with rectangular sleeve and pair of L-shaped resonator which provides a wide usable fractional bandwidth of more than 130% (3.05-14.3 GHz). By cutting a modified W-shaped slot with variable dimensions on the radiating patch frequency band-stop performance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 13 publications
(14 reference statements)
0
39
0
Order By: Relevance
“…The frequency range for UWB systems between 3.1 and 10.6 GHz will cause interference to the existing wireless communication systems, for example, the wireless local area network (WLAN) for IEEE 802.11a operating in 5.15–5.35 GHz and 5.725–5.825 GHz bands, so the UWB antenna with a band‐stop performance is required. Recently, to generate the frequency band‐notch function, modified planar monopoles have been recently proposed [5–9]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency range for UWB systems between 3.1 and 10.6 GHz will cause interference to the existing wireless communication systems, for example, the wireless local area network (WLAN) for IEEE 802.11a operating in 5.15–5.35 GHz and 5.725–5.825 GHz bands, so the UWB antenna with a band‐stop performance is required. Recently, to generate the frequency band‐notch function, modified planar monopoles have been recently proposed [5–9]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. 5–7, different shapes of the slots (i.e., square ring with a pair of T‐shaped strips protruded inside it, W‐shaped and folded trapezoid) are used to obtain the desired band notched characteristics. Single and multiple [8] half‐wavelength U‐shaped slots are embedded in the radiation patch to generate the single and multiple band‐notched functions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication [8], Yazdanifard et al have demonstrated a new stepped square monopole antenna with W shaped slot and a ground plane with rectangular sleeves and a pair of L-shaped resonator for an ultra wide bandwidth of 130% . In yet another recent publication [9], a square monopole antenna is presented with a pair of T-shaped slot and a ground plane with a pair of rectangular sleeves and T-shaped resonator to provide an ultra wide fractional bandwidth of more than 125% (3.05-13.57 GHz).…”
Section: Introductionmentioning
confidence: 99%
“…A few good examples of UWB antennas may also be found in [11][12][13][14][15]. However, most of the recently reported papers give the simulated and experimental results of frequency domain characteristics of the UWB/band notched UWB antenna like return loss, VSWR, gain, radiation pattern in E plane and H plane [8][9][10][11][12][13][14][15]. In order to completely characterize a UWB antenna, time domain characteristics are also important like impulse response, signal fidelity etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, to generate the frequency band-notch function, modified planar monopoles with T-shaped conductor-backed plane [9], U-shaped slots [10], W-shaped slot, and small strip bar [11] are used.…”
Section: Introductionmentioning
confidence: 99%